Extraction technology, component analysis, antioxidant, antibacterial, analgesic and anti-inflammatory activities of flavonoids fraction from Tribulus terrestris L. leaves. Issue 8 (August 2019) - Tian, Chunlian; Chang, Yu; Zhang, Zehui; Wang, Hong; Xiao, Shibo; Cui, Cancan; Liu, Mingchun
Abstract: Research on the extraction technology, component analysis, and antioxidant, antibacterial, analgesic and anti-inflammatory activities of flavonoids fraction from Tribulus terrestris L. leaves was carried out. The extraction process was optimized by response surface method, and the maximum yield 0.27% for flavonoids fraction was achieved with concentration of ethanol solution 25.87%, ratio of solvent to material 30:1 ml/g, and ultrasonic extraction time 27.93 min. Moreover, 14 compositions were identified separately from flavonoids fraction by HPLC-DAD-ESI-MS 2 . In addition, flavonoids fraction exhibited a better antioxidant activity demonstrated by assays of ABTS, DPPH radical scavenging activity and ferric reducing antioxidant power activity. Furthermore, the antibacterial, analgesic and anti-inflammatory activities of flavonoids fraction were also proved to be stronger. Therefore, the present findings suggest that flavonoids fraction from Tribulus terrestris L. leaves can be a very interesting candidate for the research and development of natural and healthy herbal medicine for the pharmaceutical and food industries.